The Development of Audio-Visual Media for News Text Learning at SMP Negeri 2 Lawang Kidul Tanjung Enim - Desta Lingga Sari; Missriani Missriani; Arif Ardiasnyah (Yayasan Karinosseff Muda Indonesia, 2020)
This study aims to determine and identify the development of audio-visual media for news text learning at SMP Negeri 2 Lawang Kidul Tanjung Enim, to find out and identify the results of the validation of audio-visual media for news texts learning for students of SMP Negeri 2 Lawang Kidul Tanjung Enim, and to find out and identify the results of news text learning for students of SMP Negeri 2 Lawang Kidul Tanjung Enim after the application of audio-visual media. The design of audio-visual media for learning news text for students of SMP Negeri 2 Lawang Kidul Tanjung Enim which has been accepted by the experts is feasible to be tested. This study used research and development methods. The research and development steps consist of 10 stages which includes problem identification, data collection, product design (Initial Draft), expert validation, design improvement, small group trials, product revisions, large group trials, product revisions, and final production The results of the validation of media experts, material experts and language experts on the development of audio-visual media products for learning news texts for students at the State Junior High School 2 Lawang Kidul Tanjung Enim are in the very good category. Applied audio-visual media has increased the criteria for being very effective.